Trending copy culture of Bangladesh: Brand product perspective - Moutusi Tanha; Md. Al Sabahel; Md. Ruhul Amin; Md. Shahjahan Khandakar; Nayem Mahmud Bhuiyan; Md. Yeamin Masum; Jawad Md. Asadullah (goodwood publishing, 2022)
Purpose: This study aims to reveal the copy culture of Bangladesh. Research methodology: Qualitative research was designed for this study, and an ethnographic approach was used for data collection along with in-depth interviews with copy brand users. The judgmental and snowball sampling methods were used in this study. Semi-structured questionnaires and mostly open-ended questions were designed based on the objectives of this study. Results: The findings were analyzed under three main themes: Copying Us or copying them, Consumer Subjectivity as individuals, and Fragmented Authenticity. Limitations: Due to financial and time constraints, this research focused only on the capital city of Dhaka. In the case of broader research, this study can be analyzed in other regions of the country, which will provide a wide range of information regarding copy-culture attitudes. Contribution: In Bangladesh, people follow foreign trends and famous people’s lifestyles through copy brands. This study defines how and why copying culture encourages people to purchase from the local market. The reason that allures customers to buy replicate products is the availability and affordable price of the product, which is at a time creatively designed likely to match the original version. Novelty: This study can help others to take decisions based on the findings on copy culture.